ACUTE EXERCISE CHANGES THE FOURIER-TRANSFORM INFRARED SPECTRA PROFILE IN INDIVIDUALS WITH HYPERTENSION AND OTHER CARDIOVASCULAR RISK FACTORS: EFFECT OF THE SESSION DURATION. (April 2021) - Teixeira, Manuel; Lima, Suiane; Gouveia, Marisol; Duarte, Ana; Ferreira, Miriam; Simões, Maria I.; Conceição, Maria; Costa, Mariana; Nunes, Alexandra; Vieira, Sandra I.; Ribeiro, Fernando
Abstract : Objective: Evaluate the acute effects of two sessions of moderate exercise with different durations, on the metabolomic profile of adults with cardiovascular risk factors or established cardiovascular disease. Design and method: 15 adults (age: 66.5 ± 7.6 years; BMI: 26.8 ± 3.7 kg/m2; 80% women) were recruited in a community exercise program of a primary health care centre. They performed two sessions of moderate intensity aerobic (endurance) exercise with different duration periods (30 versus 45 min). Venous blood was collected before and after each exercise session. Samples were centrifuged and the plasma was used for Fourier-transform infrared (FTIR) spectroscopy analysis. The spectra were acquired, and multivariate analysis applied. Results: FTIR analysis showed good discrimination between pre- and post- the 30 min session in the 1700–1600 cm-1 region (Amide I band) and 1500–900 cm-1 region (fingerprint region). Principal component analysis of the fingerprint region revealed that the post-exercise samples presented peaks related to glycogen (1079 cm-1) and collagen (1458 cm-1, 1339 cm-1), which reflect the exercise training. Pre-exercise samples had peaks related to ribose (996 cm-1) and carbohydrates (1045 cm-1) that are sources of energy that are ready to be used during the session. Partial least squares regression of the Amide I region also showed differences after exercise. In the baseline, the participants seem to have higher levels of antiparallel β-sheets (1690 cm-1) and side chains (1611 cm-1), which are linked with proteins prone to aggregate. However, after exercise, the participants showed a peak related to random coils (1639 cm-1), which may indicate a transitional state for the β-sheet rich protein to a more stable profile. In the 45 min session no differences were observed after the session in the amide I region. Conclusions: A single aerobic exercise, irrespective of the duration, does not induce deleterious changes in the metabolomic profile. Only the 30 min session promoted a positive alteration in the quality of the proteins; this change in the quality of the proteins and the fingerprint region indicates a possible alteration associated with the duration of the exercise.